Molecular Cloning, Characterization, and Expression of Crustacean Cardioactive Peptide in Oriental River Prawn, Macrobrachium nipponense, during Acute Hypoxia and Reoxygenation. Issue 2 (14th January 2018) - Shan, Dongyan; Fu, Hongtuo; Qiao, Hui; Sun, Shengming; Zhang, Wenyi; Jin, Shubo; Jiang, Sufei; Gong, Yongsheng; Xiong, Yiwei; Wu, Yan
Abstract: A full‐length complementary DNA of the crustacean cardioactive peptide (CCAP) was cloned from the eyestalk of the oriental river prawn, Macrobrachium nipponense, and named Mn ‐CCAP. Experimental treatment was set to decrease dissolved oxygen levels and generate hypoxic culture conditions. The Mn ‐CCAP expression profile was different in the brain and eyestalk. Results suggested Mn ‐CCAP responds strongly to hypoxia‐induced oxidative stress. Different expression profiles in the brain and eyestalk indicate that these two tissues may respond in different ways to hypoxia.